UJI AKTIVITAS GEL EKSTRAK DAUN KELOR (Maringa oelifera L.) DARI KABUPATEN BLORA TERHADAP PENYEMBUHAN LUKA BAKAR PADA KELINCI New Zealand - Dina Permata Sari; Gigih Kenanga Sari; Maulita Saraswati (Joseph: Journal of Science and Pharmacy, 2022)
Background: The saponin and tannin compounds in Moringa leaf extract stimulate the formation of collagen, namely in the wound healing process and in cleaning so that it is more effective in healing burns. Purpose: The purpose of this study was to determine the effect of Moringa leaf (Moringa oleifera L.) ethanol extract gel on burn healing Method: This study aims to determine the effectiveness of Moringa leaf extract gel in healing burns in rabbits. This study used 70% ethanol and divided into 3 formulas with the same extract concentration of 9%, for positive control (Biopacenton), negative control (Extract). Results: Data analysis was carried out using one way Anova. The results showed that the ethanol extract gel of Moringa leaves (Moringa oleifera L.) with a concentration of 9% with HPMC bases of 8%, 9% and 10% , had activity on the healing of burns on the backs of New Zealand strain rabbits. Conclusion: Moringa leaf ethanol extract gel (Moringa oleifera L.) can heal burns on the backs of New Zealand rabbits.